PENGARUH KEPRIBADIAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DIMEDIASI KOMITMEN ORGANISASIONAL PADA SEKRETARIAT DAERAH KABUPATEN PATI - Haris Riyanto, 11.5202.0034 (Students Journal of Economic and Management, 2013)
The purpose of this study to determine the effect of personality and organizational culture on performance mediated by the Organizational Commitment Sekretariat Daerah Kabupaten Pati. This research was conducted with a purposive sampling method and implemented in Sekretariat Daerah Kabupaten Pati. Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. Tested the validity of data collected by viewing at the magnitude of the KMO values above 0.5 and the loading factors above 0.4 could be declared valid. The results demonstrate the validity of the KMO test for personality is 0.870, KMO test for organizational culture is 0.847. KMO test for Organizational commitment is 0.822 and KMO test for the performance is 0.922. It can be said that all variables declared valid. Its reliability test showed the 0.899 for personality, 0.947 for organizational culture, 0,872 for organizational commitment and 0.905 for performance. These show that all variables are reliable. From the analysis and discussion show that a significant positive influence personality on organizational commitment, significantly positive effect of organizational culture on organizational commitment, personality is a significant positive effect on performance, organizational culture significantly positive effect on performance and organizational commitment significantly positive effect on performance. Strong influence of personality is directly compared to the performance through the mediation of organizational commitment. Moreover of Organizational culture has strong directly influence compared toward the performance through the mediation of organizational commitment. Keywords: Personality, Organizational Culture, Organizational Commitment and Performance